2012
DOI: 10.1002/adfm.201200290
|View full text |Cite
|
Sign up to set email alerts
|

High‐Performance Top‐Gated Organic Field‐Effect Transistor Memory using Electrets for Monolithic Printed Flexible NAND Flash Memory

Abstract: High‐performance top‐gated organic field‐effect transistor (OFET) memory devices using electrets and their applications to flexible printed organic NAND flash are reported. The OFETs based on an inkjet‐printed p‐type polymer semiconductor with efficiently chargeable dielectric poly(2‐vinylnaphthalene) (PVN) and high‐k blocking gate dielectric poly(vinylidenefluoride‐trifluoroethylene) (P(VDF‐TrFE)) shows excellent non‐volatile memory characteristics. The superior memory characteristics originate mainly from re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
187
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 192 publications
(188 citation statements)
references
References 43 publications
1
187
0
Order By: Relevance
“…In particular, high-performance flexible non-volatile memories based on various data storage principles such as resistive type [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] , flash 4,[25][26][27][28][29] and ferroelectric [30][31][32][33][34][35][36][37][38][39][40] hold great promise in a variety of emerging applications ranging from mobile computing to information management and communication. While the recent advances in this area are impressive, novel organic materials and electronic device structures that can be tightly rolled, crumpled, stretched, sharply folded and unfolded repeatedly without any performance degradation still need to be developed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, high-performance flexible non-volatile memories based on various data storage principles such as resistive type [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] , flash 4,[25][26][27][28][29] and ferroelectric [30][31][32][33][34][35][36][37][38][39][40] hold great promise in a variety of emerging applications ranging from mobile computing to information management and communication. While the recent advances in this area are impressive, novel organic materials and electronic device structures that can be tightly rolled, crumpled, stretched, sharply folded and unfolded repeatedly without any performance degradation still need to be developed.…”
mentioning
confidence: 99%
“…Although significant progress has been made in improving certain characteristics of ferroelectric polymer memories [30][31][32][33][34][35] , only a few works have addressed mechanically flexible Fe-FETs in which characteristic ferroelectric switching has been examined under a relatively mild bending radius on the order of a few millimetres [36][37][38] . Besides ferroelectric memories, most of the previous non-volatile memories are categorized as bendable devices when their bending radii are much greater than 1 mm (Supplementary Table 1).…”
mentioning
confidence: 99%
“…The active semiconductors can be organic channel materials for OFETs, organic light-emitting materials for OLEDs, organic photoactive materials for OSCs, organic memory materials for OMDs. To date, great improvements have been made for achieving high performance that is comparable to their inorganic counterparts [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…18,19 It has been reported that TOMDs have memory functions from ferroelectric polymers, metal nanoparticles or charge trapping layers, and polymer energy well structures. [20][21][22][23][24][25][26][27][28][29][30] However, most TOMDs reported to date have limitations with respect to high operation voltages and/or poor retention (stability) characteristics, even though basic memory functions in transistor structures can be welldemonstrated. Thus, it is very important to achieve both low voltage and high retention characteristics at the same time for further consideration toward commercialization of TOMDs, particularly for mobile applications, of which the first priority is low power consumption, as well as stability.…”
Section: Introductionmentioning
confidence: 99%